Pentingnya Self-Compassion bagi Kesehatan Mental Individu - Apsari, Diani Akmalia; Budi Utomo, Hanggara (Psikodinamika: Jurnal Literasi Psikologi, 2024)
High prevalence of mental health cases is not followed by optimal mental health services that are accessible to most public. Individual barriers are needed such as self-compassion skills. The aim of this research is to describe the dynamics of individual self-compassion with mental health problems. This study used a qualitative approach with a systematic literature review method. The data mining using Publish and Perish for the last 5 years of research (2019-2023), was limited to English-language, and Scopus-indexed literature by excluding proceedings and book chapters. 6 literatures most relevant to the research topic were obtained from high quality databases (Taylor & Francis, Springer Link, APA, and Oxford Academic). The result is that self-compassion has an important role in the dynamics of mental health, where increasing self-compassion can contribute to better mental health. Self-compassion important for individuals to better cope with pressure and stress, and maintain good mental health. This literature review hopes to provide information the role of self-compassion as a barrier mental health problems.